2014
DOI: 10.1017/fms.2014.2
|View full text |Cite
|
Sign up to set email alerts
|

Improved Rank Bounds for Design Matrices and a New Proof of Kelly’s Theorem

Abstract: We study the rank of complex sparse matrices in which the supports of different columns have small intersections. The rank of these matrices, called design matrices, was the focus of a recent work by Barak et al. [Rank bounds for design matrices with applications to combinatorial geometry and locally correctable codes. Proceedings of the 43rd annual ACM symposium on Theory of computing, STOC 11, (ACM, NY 2011), 519-528] in which they were used to answer questions regarding point configurations. In this work, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
78
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3
1

Relationship

5
2

Authors

Journals

citations
Cited by 35 publications
(80 citation statements)
references
References 33 publications
(67 reference statements)
2
78
0
Order By: Relevance
“…, S m and the fact that together they cover pairs from a quadratic number of triples. This should be contrasted with the results of [BDWY11,DSW12] which prove strong lower bounds for q-LCC's (for any constant q) in which every pair is in a bounded number of triples (these are called 'design' LCCs).…”
Section: Each Triple In Each Matching M V Has Two Of Its Elements In mentioning
confidence: 93%
See 3 more Smart Citations
“…, S m and the fact that together they cover pairs from a quadratic number of triples. This should be contrasted with the results of [BDWY11,DSW12] which prove strong lower bounds for q-LCC's (for any constant q) in which every pair is in a bounded number of triples (these are called 'design' LCCs).…”
Section: Each Triple In Each Matching M V Has Two Of Its Elements In mentioning
confidence: 93%
“…While this has not materialized yet, it motivated the invention of multiplicity codes by [KSY11] which are new LCCs of high rate, and turn out to yield optimal list-decodable codes as well [Kop12] . Finally, since the work of [DS06], LDCs and LCCs have played a role in understanding basic problems in Polynomial Identity Testing and established its connection to problems in Incidence Geometry, e.g [KS09, BDWY11,DSW12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Strangely, while these vectors provide an LDC over every field, they fail to be an LCC except over F 2 . This gap was first explained in [5,15] where the authors showed that over the real numbers (and indeed even over large enough finite fields), 2-LCCs simply do not exist! For every error-rate δ the dimension d for which such codes exist is finite, and cannot exceed poly(1/δ ).…”
mentioning
confidence: 99%